Hydrogels that listen to cells: a review of cell-responsive strategies in biomaterial design for tissue regeneration. Issue 6 (29th September 2017) - Ooi, H. W.; Hafeez, S.; van Blitterswijk, C. A.; Moroni, L.; Baker, M. B.
Abstract : This review discusses the recent advances and design principles for dynamic and cell-responsive hydrogels – biomaterials that respond to locally produced stimuli in and around cells or tissues without external influence. Abstract : The past decade has seen a decided move from static and passive biomaterials to biodegradable, dynamic, and stimuli responsive materials in the laboratory and the clinic. Recent advances towards the rational design of synthetic cell-responsive hydrogels—biomaterials that respond locally to cells or tissues without the input of an artificial stimulus—have provided new strategies and insights on the use of artificial environments for tissue engineering and regenerative medicine. These materials can often approximate responsive functions of a cell's complex natural extracellular environment, and must respond to the small and specific stimuli provided within the vicinity of a cell or tissue. In the current literature, there are three main cell-based stimuli that can be harnessed to create responsive hydrogels: (1) enzymes (2) mechanical force and (3) metabolites/small molecules. Degradable bonds, dynamic covalent bonds, and non-covalent or supramolecular interactions are used to provide responsive architectures that enable features ranging from cell selective infiltration to control of stem-cell differentiation. The growing ability to spatio-temporally control the behavior of cells and tissue with rationally designed responsive materials has the ability to allow control and autonomy to future generations of materials for tissue regeneration, in addition to providing understanding and mimicry of the dynamic and complex cellular niche.